On aliovalent cations control of α-alumina growth on doped and undoped NiAl. (15th May 2021) - Boll, Torben; Babic, Vedad; Panas, Itai; Bäcke, Olof; Stiller, Krystyna
Abstract: Alumina forming Ni-base superalloys are essential due to their oxidation resistance at elevated temperatures. A two-step procedure allows to assess the outward growth of the oxide scale from the resulting oxide ridges that form at 1100°C and cap the alumina grain boundaries. Employing undoped 50Ni50Al (at%) as reference, the impact of reactive elements on the diffusion processes, here Zr and Hf, is quantified using atom probe tomography. Unexpectedly, we find that up to one monolayer of Ni may co-decorate the alumina grain boundaries. Additionally, a decrease in Al-, and Ni-diffusivity of two orders of magnitude is observed owing to the reactive element effect. We employ density functional theory calculations to better understand the role of aliovalent cations, here Ni(II), Zr(IV), and Hf(IV) in the α−alumina scale. The calculations show that Ni may not only decorate the alumina grain boundaries but also facilitates transport of electrons as well as oxygen vacancies. Thereby oxide scale growth becomes enhanced. In turn, the dual impact of reactive elements, i.e. to annihilate oxygen vacancies and to remove impurity states in the band gap, explains the reduced scale growth rate. Graphical abstract: Image, graphical abstract